Women and Leadership Roles in the Academic Sector : An Analysis within Public and Private Educational Institutes in Malaysia. - Tanuwidjaja, Jojico (2011)
Although women academics in the Malaysian context have made enormous gains in leadership positions in the past decade, they are still under-represented in more ways than one. In brief, the road to senior academic leadership positions seems to be long and winding for these women both in the public and private educational institutes. Why does it seem that women academics take a longer period to climb the academic ladder or not at all? What are the factors holding women academics back? This paper aims to answer such ambiguities through the use of in-depth interviews of women academics from various fields of specialisation. More often than not, women‘s career paths generally do not follow the conventional trajectory long established by successful men academicians. In attempt to investigate the factors causing women‘s slower progression through the academic hierarchy, it is discovered that women usually take an exit at some point in time. Most respondents noted that they have left the fast lane to make the personal choice between career and parenting, and many find themselves at the back of the pack when they re-enter the academic highway. Including many other factors that play the role of hampering women academics‘ career, it is obvious that they will face vertical segregation or a double-glazing glass ceiling of either family obligations or a system that would deter them from going upwards. Besides, this paper also proposes ways that women can overcome the issue of vertical segregation if and when they are put into situations where career immobility is present. Amongst other solutions that will be discussed, mentoring and networking are two most essential communication channels that may potentially assist women in climbing the academic ladder. As respondents have highlighted, building these relationships are as important as bettering themselves in terms of merits and qualifications. The third major finding that completes this paper is the conclusion of educational institutes in Malaysia that are deficient in terms of women-friendly human resource policies. The current practices are not necessarily aimed at discriminating against women but have been implemented without women in mind. However, other policies relating to tenure, promotion and recruitment has been executed in ways which creates an even field for both men and women academicians. All in all, even though efforts have been put into place, the rate at which institutes in Malaysia have been advocating for women‘s empowerment is still very much in its adolescent stage.